2022
DOI: 10.1186/s12864-022-08459-y
|View full text |Cite
|
Sign up to set email alerts
|

The genomic basis of the Streptococcus thermophilus health-promoting properties

Abstract: Background Streptococcus thermophilus is a Gram-positive bacterium widely used as starter in the dairy industry as well as in many traditional fermented products. In addition to its technological importance, it has also gained interest in recent years as beneficial bacterium due to human health-promoting functionalities. The objective of this study was to inventory the main health-promoting properties of S. thermophilus and to study their intra-species diversity at the genomic and genetic level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 207 publications
(206 reference statements)
0
11
0
Order By: Relevance
“…In this study, both genomes were analysed independently. ** The identification name of the strains of Streptococcus thermophilus STH_CIRM_1048 and Streptococcus thermophilus STH_CIRM_1049 is related to the accession codes for genomes valid for the NCBI database; the same strains are reported as Streptococcus thermophilus CIRM-BIA1048 Streptococcus thermophilus CIRM-BIA1049 in citation [ 32 , 33 ]. *** GenBank code PEBN01000000.1 and PEBN01000052.1 both refer to Streptococcus macedonicus 19AS strain in NCBI database.…”
Section: Figurementioning
confidence: 99%
“…In this study, both genomes were analysed independently. ** The identification name of the strains of Streptococcus thermophilus STH_CIRM_1048 and Streptococcus thermophilus STH_CIRM_1049 is related to the accession codes for genomes valid for the NCBI database; the same strains are reported as Streptococcus thermophilus CIRM-BIA1048 Streptococcus thermophilus CIRM-BIA1049 in citation [ 32 , 33 ]. *** GenBank code PEBN01000000.1 and PEBN01000052.1 both refer to Streptococcus macedonicus 19AS strain in NCBI database.…”
Section: Figurementioning
confidence: 99%
“…The texture and flavor of fermented oat beverages dominate consumer acceptance and sustainability. Streptococcus thermophilus is derived from dairy products and considered a “Generally Recognized as Safe“ ingredient because of its ability to increase the viscosity of dairy products, Streptococcus thermophilus is often paired with Lactobacillus bulgaricus ( L. bulgaricus ) in some important fermented dairy products, including yogurt and cheese, resulting in its unique taste and stickiness [ 48 ]. Previous studies have shown that Streptococcus thermophilus TKM3 KKP 2030P is an efficient initial strain for the fermentation of plant-based raw materials.…”
Section: Strainsmentioning
confidence: 99%
“…Bulgaricus , and these genes confer survival advantage in the dairy environment (Bolotin et al., 2004; Pastink et al., 2009; Pfeiler & Klaenhammer, 2007). Moreover, most strain‐specific health‐promoting properties of S. thermophilus seem to have been likewise acquired via HGT events (Roux et al., 2022). The mechanism of HGT also seems to play a large role in the adaptability of Lact.…”
Section: Evolution Dynamics Of Labmentioning
confidence: 99%